Admission neutrophil–lymphocyte ratio predicts 90 day outcome after endovascular stroke therapy. (11th October 2013) - Brooks, Steven D; Spears, Chauncey; Cummings, Christopher; VanGilder, Reyna L; Stinehart, Kyle R; Gutmann, Laurie; Domico, Jennifer; Culp, Stacey; Carpenter, Jeffrey; Rai, Ansaar; Barr, Taura L
Abstract : Objective: Immune dysregulation influences outcome following acute ischemic stroke (AIS). Admission white blood cell (WBC) counts are routinely obtained, making the neutrophil–lymphocyte ratio (NLR) a readily available biomarker of the immune response to stroke. This study sought to identify the relationship between NLR and 90 day AIS outcome. Methods: A retrospective analysis was performed on patients who underwent endovascular therapy for AIS at West Virginia University Hospitals, Morgantown, West Virginia. Admission WBC differentials were analyzed as the NLR. Stroke severity was measured by the National Institutes of Health Stroke Scale (NIHSS) score and outcome by the modified Rankin Scale (mRS) score at 90 days. Univariate relationships between NLR, age, NIHSS, and mRS were established by correlation coefficients; the t test was used to compare NLR with recanalization and stroke location (anterior vs posterior). Logistic regression models were developed to identify the ability of NLR to predict mRS when controlling for age, recanalization, and treatment with IV tissue plasminogen activator (tPA). Results: 116 patients were reviewed from 2008 to 2011. Mean age of the sample was 67 years, and 54% were women. Mean baseline NIHSS score was 17 and 90 day mRS score was 4. There was a significant relationship between NLR and mRS (p=0.02) that remained when controlling for age, treatment with IV tPA, and recanalization. NLR ≥5.9 predicted poor outcome and death at 90 days. Conclusions: This study shows that the NLR, a readily available biomarker, may be a clinically useful tool for risk stratification when evaluating AIS patients as candidates for endovascular therapies.